SENSITIVITY AND SPECIFICITY OF INDIVIDUAL BERG BALANCE ITEMS COMPARED WITH THE TOTAL SCORE TO PREDICT FALLS IN COMMUNITY DWELLING ELDERLY INDIVIDUALS (International Journal of Physiotherapy, 2014)
Background: Falls are a major problem in the elderly leading to increased morbidity and mortality in this population. Scores from objective clinical measures of balance have frequently been associated with falls in older adults. The Berg Balance Score (BBS) which is a frequently used scale to test balance impairments in the elderly ,takes time to perform and has been found to have scoring inconsistencies. The purpose was to determine if individual items or a group of BBS items would have better accuracy than the total BBS in classifying community dwelling elderly individuals according to fall history.Method: 60 community dwelling elderly individuals were chosen based on a history of falls in this cross sectional study. Each BBS item was dichotomized at three points along the scoring scale of 0 – 4: between scores of 1 and 2, 2 and 3, and 3 and 4. Sensitivity (Sn), specificity (Sp), and positive (+LR) and negative (-LR) likelihood ratios were calculated for all items for each scoring dichotomy based on their accuracy in classifying subjects with a history of multiple falls. These findings were compared with the total BBS score where the cut-off score was derived from receiver operating characteristic curve analysis.Results: On analysing a combination of BBS items, B9 and B11 were found to have the best sensitivity and specificity when considered together. However the area under the curve of these items was 0.799 which did not match that of the total score (AUC= 0.837). A, combination of 4 BBS items - B9 B11 B12 and B13 also had good Sn and Sp but the AUC was 0.815. The combination with the AUC closest to that of the total score was a combination items B11 and B13. (AUC= 0.824). hence these two items can be used as the best predictor of falls with a cut off of 6.5 The ROC curve of the Total Berg balance Scale scores revealed a cut off score of 48.5.Conclusion: This study showed that combination of items B11 and B13 may be best predictors of falls in the elderly with a cut off of 6.5.